REGIONAL-SPECIFIC ASPECTS OF THE EPIDEMIOLOGY AND RISK CHARACTERIZATION OF MAIN NON-COMMUNICABLE DISEASES IN THE RURAL POPULATION OF MEN AND WOMEN OF ANDIJAN (World Bulletin of Public Health, 2026)
Major chronic non-communicable diseases (cardiovascular diseases, tumors, chronic respiratory diseases) have been among the most widespread diseases in the world for the past few years, and they remain the leading object of science and practice as the main cause of the therapeutic continuum among the population. Therefore, in the current era, preventive and prophylactic medicine, both theoretically and practically, and primarily in relation to major non-communicable diseases, has become an urgent issue and a necessity. According to the World Health Organization, "the annual mortality rate from them is 71%, and economic losses are about 1 trillion per year
Keywords: major noncommunicable diseases; epidemiological studies; risk factors